2014
DOI: 10.1109/tmi.2014.2314712
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Neuroanatomical Basis of Cognitive Impairment in Alzheimer's Disease by Correlation- and Nonlinearity-Aware Sparse Bayesian Learning

Abstract: Predicting cognitive performance of subjects from their magnetic resonance imaging (MRI) measures and identifying relevant imaging biomarkers are important research topics in the study of Alzheimer’s disease (AD). Traditionally, this task is performed by formulating a linear regression problem. Recently, it is found that using a linear sparse regression model can achieve better prediction accuracy. However, most existing studies only focus on the exploitation of sparsity of regression coefficients, ignoring us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…There are, however, a few examples of studies that are indeed “predicting” specific values of the target measures. For example, Wan et al has proposed an elegant regression model called CORNLIN (Wan et al, 2014) that employs a sparse Bayesian learning algorithm to predict multiple cognitive scores based on 98 structural MRI regions of interests (ROIs) for Alzheimer’s disease patients. The polynomial model used in CORNLIN can detect either a nonlinear or linear relationship between brain structure and cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, a few examples of studies that are indeed “predicting” specific values of the target measures. For example, Wan et al has proposed an elegant regression model called CORNLIN (Wan et al, 2014) that employs a sparse Bayesian learning algorithm to predict multiple cognitive scores based on 98 structural MRI regions of interests (ROIs) for Alzheimer’s disease patients. The polynomial model used in CORNLIN can detect either a nonlinear or linear relationship between brain structure and cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…Ten widely used clinical/cognitive assessment scores [3, 20, 21] were employed in this study, including Alzheimer's Disease Assessment Scale (ADAS) cognitive total score, Mini Mental State Exam (MMSE) score, Rey Auditory Verbal Learning Test (RAVLT) involving total score of the first 5 learning trials (TOTAL), Trial 6 total number of words recalled (TOT6), 30-minute delay score (T30), and 30-minute delay recognition score (RECOG), FLU involving animal total score (ANIM) and vegetable total score (VEG), and TRAILS including Trail Making test A score and B score.…”
Section: Resultsmentioning
confidence: 99%
“…Regression analyses were commonly used to predict cognitive scores from imaging measures. The relationship between commonly used cognitive measures and structural changes with MRI has been previously studied by regression models and the results demonstrated that there exists a relationship between baseline MRI features and cognitive measures [3, 4]. For example, Wan et al proposed an elegant regression model called CORNLIN that employs a sparse Bayesian learning algorithm to predict multiple cognitive scores based on 98 structural MRI regions of interests (ROIs) for Alzheimer's disease patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alzheimer Disease is a chronic Neuro-degenerative disorder that has ranked as third most expensive disease and sixth leading cause of death in United States. It is neurodegenerative disorder characterized by rapid impairment of memory and some other cognitive functions, which are mainly associated with the behavioral disturbances and finally leads to total dependency [3]. An important research is to identify the neuroanatomical basis of cognitive impairment in Alzheimer Disease (AD).…”
Section: Introductionmentioning
confidence: 99%